Growth Pattern and Degradation Activity of Caffeine-degrading Bacteria Consortium - Suksma, Nadhea Ayu; Utarti, Esti; Arimurti, Sattya (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Caffeine-degrading bacteria can be used as agents to degrade caffeine, thereby reducing the concentration of caffeine in organic waste. The decomposition process is carried out by a single bacterium or a consortium of bacteria. Caffeine-degrading bacteria from Sempol, Bondowoso, namely Acinetobacter gerneri KAFS 47, Paracoccus denitrificans KAFS 16 and Pseudomonas plecoglossicida KAFS 34, could be used as a bacterial consortium to promote caffeine degradation. The aim of this study was to analyze associations between caffeine-degrading bacteria isolates, bacterial resistance to antibiotics, growth patterns, and caffeine degradation of a consortium of caffeine-degrading bacteria, and the correlation of bacterial growth with caffeine degradation. The research method used is an analysis of the association between isolates, the development of bacterial consortium growth patterns, and their analysis based on antibiotic resistance, patterning of caffeine degradation, and correlation test (Pearson) of bacterial growth with caffeine degradation. The result of the association test between bacteria showed that the three bacteria had the potential to be used as a consortium of caffeine-degrading bacteria. A. Gerneri, P. denitrificans, and P. plecoglossicida were resistant to the antibiotic cefixime (100 ppm), erythromycin (50 ppm), lincomycin (50 ppm), metronidazole (50 ppm), and sanprima (50 ppm). The growth of the bacterial consortium (54.779 CFU/mL) was higher than that of P. plecoglossicida (49.277 CFU/mL) and lower than that of A. gerneri (93.481 CFU/mL) and P. denitrificans (84.940 CFU/mL) in incubation time of 4 days. However, the consortium of bacteria and P. plecoglossicida were able to degrade caffeine 24 hours faster (3 days) than the other two single isolates (4 days) to degrade 2.5 g/L caffeine in media to 0%. Bacterial growth due to caffeine degradation has a perfect correlation value (>0. 950) and is negative.